Event Attendance System for SIRIM Berhad - Shukri, Sofiya; Mohd Nawi, Prof Dr Nazri (Applied Information Technology And Computer Science, 2025)
SIRIM Berhad is an industrial research and technology organization in Malaysia. The organization is currently using the manual method in taking attendance for events. However, the current method is prone to errors and time-consuming. Event attendance management is a critical aspect for organizations to ensure efficient operations. The event attendance system for SIRIM Berhad is an event management system to manage attendance for all its attendees. This project focuses on the development of a QR based event attendance system for SIRIM Berhad. Thus, this web-based system was developed to facilitate event managers to track attendance during events. This system is designed into one section which is an administrator section and 6 modules which are user authentication module, event creation and management module, attendance recording real-time module, registration management module, reporting and analytics module, payment module and notifications and reminder module. This project is implemented using Prototype Model methodology, MySQL as the database, PHP as the server-side scripting and HTML to create pages. The event attendance system will be an ideal way to handle attendance issues because it will allow attendance to be taken by scanning the QR code. Therefore, an event that operates without errors will enhance user’s experience and streamlining the check-in process.